Peran Orang Tua dalam Pencegahan Tindak Kejahatan Penculikan Anak - Selviana Teras Widy Rahayu; Afendra Eka Saputra (Journal on Education, 2024)
Today's rapid social changes often give rise to various social problems. Both in terms of crime and the decline in the level of public awareness of the surrounding environment. The aim of this research is to provide direction on the role of parents in supervising their children and efforts to overcome this. This research uses a qualitative research method with a descriptive analytical approach, data collection methods by analyzing library sources. The results of this research show that children are very vulnerable to becoming victims of a crime. This is due to the child's helplessness. One of the crimes that often occurs against children is kidnapping. We can see it on social media, even if it smells like a hoax, it still causes anxiety for parents. There are various modes used when wanting to carry out these crimes. First, the mode of inviting children to play is to build close interactions with children so that children do not feel afraid. Apart from that, there are also those who disguise themselves as online motorcycle taxi drivers. The hope is that parents will become more alert and that society will be more concerned in anticipating child abduction.